2013
DOI: 10.2494/photopolymer.26.239
|View full text |Cite
|
Sign up to set email alerts
|

Precise Synthesis of Acrylic Block Copolymers and Application to On-demand Dismantlable Adhesion Systems in Response to Photoirradiation and Postbaking

Abstract: High-molecular-weight and functional acrylic block copolymers containing both the reactive and polar repeating units were synthesized using organotellurium-mediated living radical polymerization (TERP) technique. The block copolymers consisted of poly(tert-butyl acrylate) as the reactive segment and the random copolymer sequence containing n-butyl, 2-ethylhexyl, and 2-hydroxyethyl acrylate repeating units as the adhesive segment. The block copolymers exhibited high performance for the dismantlable adhesion res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…After the dismantling treatment, the polymers containing HEA units, R1 and B1, turned into insoluble in acetone, whereas the polymer without a HEA unit, B2, was soluble in acetone. We previously reports that acrylic polymers containing HEA units undergo transesterification in the presence of an acid catalyst and result in cross-linking [5,6]. The fact that B2 is soluble after the dismantling treatment shows that cross-linking by dehydration of carboxyl groups does not proceed under the current conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the dismantling treatment, the polymers containing HEA units, R1 and B1, turned into insoluble in acetone, whereas the polymer without a HEA unit, B2, was soluble in acetone. We previously reports that acrylic polymers containing HEA units undergo transesterification in the presence of an acid catalyst and result in cross-linking [5,6]. The fact that B2 is soluble after the dismantling treatment shows that cross-linking by dehydration of carboxyl groups does not proceed under the current conditions.…”
Section: Resultsmentioning
confidence: 99%
“…High molecular weight of acrylic block copolymers consisting of a PtBA and an appropriate soft segment showed good adhesion properties as a pressure sensitive adhesive (PSA) and resulted in marked decrease in peel strength after side-chain reactions, i.e., after dismantling treatment [5,6]. After dismantling, some block copolymers resulted in interfacial failure between an adhesive polymer and a polyethylene terephthalate (PET) support film, whereas random copolymers having similar compositions to the block copolymers brought about insufficient decrease in the peel strength and stick-slip failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently we reported pressure-sensitive adhesive (PSA) type dismantlable adhesive systems responding to dual stimuli, UV irradiation and subsequent heating, using reactive acrylic copolymers containing tert-butyl acrylate (tBA) and 2-hydroxyethyl acrylate (HEA) units [14][15][16][17][18]. It was revealed that tBA and HEA units in the copolymers undergo deprotection and transesterification, respectively, and the reactions are catalyzed by acids [14,16]. Therefore, a photo-acid generator (PAG) was utilized instead of an acid in order to achieve high thermal stabilities before acid generation and high reactivities after acid generation by photoirradiation.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported a dismantlable adhesive system using degradable polyperoxides as curable and pressure-sensitive adhesives and the control of bonding strength by the radical chain degradation of the polyperoxide adhesives [16][17][18]. More recently, we developed an advanced system using acrylic polymers containing t-butyl acrylate (tBA) unit in order to overcome the dilemma of reliable adhesion property during use and the subsequent quick debonding [19][20][21][22][23][24]. The tBA-containing polymers were demonstrated to function as the dismantlable adhesive materials due to a facile transformation to polymers including acrylic acid repeating units, accompanied by the elimination of isobutene gas, under the appropriate photo irradiation conditions followed by postbaking at a desired temperature.…”
mentioning
confidence: 99%